Micron-sized rare earth cerium additive modified 1000MPa-grade high-strength steel submerged-arc welding flux as well as preparation method and application thereof

By introducing micron-grade rare earth cerium additives into the submerged arc welding flux of 1000MPa grade high-strength steel, a uniform and fine composite inclusions are generated, which solves the problem of lower low-temperature toughness of the deposited metal and high tendency to cracks during welding of high-strength steel, and achieves high strength and high toughness of the weld.

CN119525822APending Publication Date: 2025-02-28HARBIN WELL WELDING CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411848539.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing 1000MPa grade high-strength steel submerged arc welding welded metal has problems such as low low temperature toughness, high tendency to produce cracks, and burning of alloy elements.

Method used

The 1000MPa grade high-strength steel submerged arc welding flux modified with micron-level rare earth cerium additive is used to produce uniform and fine composite inclusions by introducing cerium elements, refine grains, increase residual austenite content and dispersion, and improve the strength and toughness of the deposited metal.

Benefits of technology

It significantly improves the impact toughness of the deposited metal, reduces the tendency of cracks, enhances the mechanical properties stability of the weld, and reduces the possibility of local overheating and concentrated burning during the welding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention provides a micron-sized rare earth cerium additive modified 1000MPa-grade high-strength steel submerged-arc welding flux as well as a preparation method and application thereof, and belongs to the technical field of flux preparation. The invention solves the problems of low low-temperature toughness, high crack generation tendency, burning loss of alloy elements and the like of the existing 1000MPa-grade high-strength steel submerged-arc welding deposited metal. The rare earth cerium additive is introduced into the welding flux, the additive can improve the fluidity of the welding flux so as to improve the welding quality, meanwhile, micron-sized rare earth cerium has the effects of refining grains and modifying inclusions, and the micron-sized rare earth cerium is matched with other components in the welding flux so that the strength of deposited metal can be enhanced, and the low-temperature impact toughness of the deposited metal can be improved. The flux can be used for welding 1000MPa-grade high-strength steel under the working conditions that the online energy is greater than 30kJ / cm and the thickness of a base metal plate is greater than 80mm, the mechanical property of deposited metal after welding is excellent, the construction cost of the high-strength steel for water-power engineering can be reduced, and the flux has remarkable economic benefits and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flux preparation, and specifically relates to a 1000MPa high-strength steel submerged arc welding flux modified by a micron-level rare earth cerium additive, a preparation method and an application thereof. Background Art

[0002] Hydropower has many advantages, such as environmental protection and pollution-free, significant economic benefits, outstanding social comprehensive benefits, energy security and stability, mature and reliable technology, and conducive to ecological and environmental protection, and has played an important role in the development of green economy. In order to increase the capacity of hydropower, hydropower organizations continue to improve the speed, efficiency and capacity of generator sets, which puts higher requirements on the performance of water diversion pressure pipes and hydropower steel such as ribs, bifurcated pipes and volutes. Therefore, high-strength steel is continuously used in the construction of hydropower stations, and has gradually developed from the early 500MPa grade to the 1000MPa grade. However, in the development of welding materials related to 1000MPa high-strength steel for hydropower, the difficulty of research and development is the matching of large thick plate welding materials and the high strength and toughness of its deposited metal and low crack tendency.

[0003] Existing patent CN116638221A discloses a welding wire, flux, preparation method and welding method for high-wire energy submerged arc welding of 1000MPa high-strength steel, and the low-temperature -60°C impact toughness of the deposited metal is about 60J; patent CN108637527A discloses a sintered flux for submerged arc welding of 1000MPa high-strength steel with added rare earth elements, but the rare earth element is included in the flux by weight 2 to 7 parts, the amount is large, and the welding cost is increased.

[0004] In summary, the existing submerged arc welding materials for 1000MPa high-strength steel still have problems such as reduced low-temperature toughness, high tendency to crack, and burnout of alloy elements. Summary of the invention

[0005] In order to solve the problems of low low-temperature toughness, high tendency to crack generation, and burnout of alloy elements in the existing 1000MPa high-strength steel submerged arc welding deposited metal, the present invention provides a 1000MPa high-strength steel submerged arc welding flux modified with a micron-level rare earth cerium additive, a preparation method and an application thereof.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] One of the purposes of the present invention is to provide a 1000MPa grade high strength steel submerged arc welding flux modified by a micron grade rare earth cerium additive, the chemical composition of the flux, by weight percentage, comprises: CaF 2 : 23~29%, MgO: 28~35%, SiO 2 :8~15%,Al 2 O3 :14~20%, CaO: 6~10%, TiO 2 : 5%, K 2 O+Na 2 O: 5-10%, MnO: ≤4%, micron-sized rare earth cerium additive: ≤2%

[0008] Further limiting, K 2 O+Na 2 O in K 2 O and Na 2 The mass ratio of O is 1:3.

[0009] It is further defined that the micron-sized rare earth cerium additive in the flux is 1-2% by weight.

[0010] The second object of the present invention is to provide a method for preparing a 1000MPa grade high-strength steel submerged arc welding flux modified by a micron-grade rare earth cerium additive, comprising:

[0011] (1) preparing high-purity cerium trifluoride by chemical reaction method, and then subjecting the cerium trifluoride to ultrasonic washing, drying, step temperature calcination, grinding, screening, ball milling, and secondary screening to obtain a micron-grade rare earth cerium additive;

[0012] (2) In addition to the micron-sized rare earth cerium additive, K 2 O+Na 2 The other ingredients except O are mixed and canned according to the flux formula, and the mixing can is placed in a mixer filled with rare gas for dry mixing;

[0013] (3) loading the micron-sized rare earth cerium additive into an atomizer, connecting the atomizer to a mixer, and simultaneously starting the atomization and stirring process to atomize the micron-sized rare earth cerium additive into tiny particles and fully mix them with other components in the flux;

[0014] (4) After atomization, add K 2 O+Na 2 O is stirred, and after being stirred evenly, the flux is obtained through granulation, low-temperature drying, low-temperature screening, high-temperature drying, high-temperature screening, cooling and packaging steps.

[0015] It is further defined that the purity of cerium trifluoride obtained by the chemical reaction method in (1) is greater than 99.95%.

[0016] It is further defined that the drying temperature in (1) is 100-200° C. and the drying time is 6 h.

[0017] It is further defined that (1) the medium-step temperature calcination system is 500°C / 2h+700°C / 2h+900°C / 2h+1200°C / 2h.

[0018] It is further defined that the mesh sizes of the sieving in (1) are 50, 80, 100 and 150 meshes respectively.

[0019] It is further defined that the mesh size of the secondary screening in (1) is 200 mesh.

[0020] It is further defined that the grinding, screening, ball milling and secondary screening in (1) are all carried out at room temperature and low humidity.

[0021] It is further defined that (1) the low to medium humidity condition is an ambient humidity of less than 50%.

[0022] It is further defined that (1) the particle size of the medium-micron rare earth cerium additive is 50 to 100 μm.

[0023] It is further defined that (1) the melting point of the medium-micron rare earth cerium additive is 900-1640°C.

[0024] It is further defined that the dry stirring time in (2) is 5 to 10 minutes and the rotation speed is 120 revolutions per minute.

[0025] It is further defined that the atomization pressure in the atomization process in (3) is 3.5 to 5.0 MPa.

[0026] It is further defined that the stirring time in (3) is 20 min and the rotation speed is 60 rpm.

[0027] It is further defined that the medium and low temperature drying temperature in (4) is 200-300°C.

[0028] It is further defined that (4) the low temperature screening mesh size is 12 to 50 meshes.

[0029] It is further defined that the medium-high temperature drying temperature (4) is 750-850°C.

[0030] It is further defined that (4) the medium and high temperature screening mesh size is 12 to 50 meshes.

[0031] The third object of the present invention is to provide an application of the 1000MPa high-strength steel submerged arc welding flux modified by the above-mentioned micron-sized rare earth cerium additive, and specifically the flux is used for welding 1000MPa high-strength steel in hydropower engineering.

[0032] The welding conditions are further defined as: high line energy with energy greater than 30 kJ / cm, and thick plate conditions with plate thickness greater than 80 mm.

[0033] It is further specified that the deposited metal used for welding of 1000MPa grade high-strength steel in hydropower projects has a tensile strength of ≥950MPa, a yield strength of ≥820MPa, an impact absorption energy of ≥85J at -40°C, and an impact absorption energy of ≥70J at -60°C.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The present invention regulates the composition of the flux and introduces cerium into the flux. The cerium element produces uniform and fine composite inclusions, refines the grains, forms a large amount of stable acicular ferrite in the welding process, increases the content and dispersibility of residual austenite, improves the strength and toughness of the deposited metal, and makes the weld after welding beautiful in shape, easy to remove slag, smooth in transition, free of solidification cracks, and excellent in crack resistance. Under the principle of low-strength matching, the impact toughness of the deposited metal is greatly improved. The flux of the present invention is used to weld 1000MPa grade high-strength steel under the working conditions of online energy greater than 30kJ / cm and base material plate thickness greater than 80mm. The tensile strength of the deposited metal obtained is ≥950MPa, the yield strength is ≥820MPa, the impact absorption energy of the Charpy pendulum test at -40℃ is ≥85J, and the impact absorption energy of the Charpy pendulum test at -60℃ is ≥70J, which is higher than the impact absorption energy of the Charpy pendulum test at -40℃ required by most projects, ≥47J, leaving a large margin to cope with more complex applications and working conditions.

[0036] (2) The present invention modifies the submerged arc welding flux by adding an appropriate amount of rare earth cerium, and uses the modified flux to weld 1000MPa grade high-strength steel. The proportion of residual austenite in the obtained deposited metal increases. When the residual austenite is subjected to high-speed impact, it induces a plastic effect through phase transformation, thereby causing a martensitic phase transformation, which greatly improves the plasticity of the deposited metal. In addition, the addition of micron-level rare earth cerium can also adjust the melting point of the flux through interaction with other elements, thereby lowering the melting point of the flux and making it easier to melt and flow during welding.

[0037] (3) The cerium element in the flux of the present invention has good chemical activity and a strong affinity for impurity elements such as oxygen and sulfur. During the welding process, it can form high-melting-point sulfides and oxides with them and precipitate from the welding slag. Rare earth cerium can also form stable compounds with other elements such as Cr, Ni, and C, which helps to evenly distribute the flux components. Uniform flux components are beneficial to improving the fluidity of the flux and ensuring the stability of the welding process.

[0038] (4) The performance of the deposited metal after welding high-strength steel using the flux provided by the present invention meets the actual engineering application requirements of 1000MPa grade high-strength steel, and effectively solves the problem of reduced low-temperature toughness of the deposited metal when welding 1000MPa grade high-strength steel.

[0039] (5) The present invention not only introduces rare earth cerium into the flux, but also has a small particle size of the rare earth cerium additive, so its surface area will be increased, which is conducive to the uniform distribution of rare earth cerium in the welding material and reduces the possibility of local overheating and concentrated burning during welding; in addition, the rare earth cerium additive reduces the melting point and viscosity of the flux by interacting with other flux components, which helps the stable existence and transition of rare earth cerium in the deposited metal, further reduces burning, and increases the transition coefficient of cerium. The larger transition coefficient and relatively small amount of rare earth cerium added make it easier to control the cerium content in the submerged arc welding deposited metal produced by the flux provided by the present invention, preventing the precipitation of grain boundary brittle phases that reduce impact toughness due to excessive addition of rare earth cerium, thereby enhancing the mechanical property stability of 1000MPa grade high-strength steel deposited metal and weld. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The metallographic microstructure of the deposited metal of Example 1 (observed at 500 times magnification using a metallographic microscope);

[0041] Figure 2 The metallographic microstructure of the deposited metal of Comparative Example 1 (observed at 500 times magnification using a metallographic microscope);

[0042] Figure 3 This is a microscopic morphology of the deposited metal of Example 1 (observed using a scanning electron microscope at a magnification of 3000 times);

[0043] Figure 4 This is a scanning image of the impact fracture of the deposited metal of Example 1 (magnified 5000 times);

[0044] Figure 5 This is a scanning image of the impact fracture of the deposited metal of Comparative Example 2 (magnified 5000 times);

[0045] Figure 6 EBSD image of the deposited metal of Example 1;

[0046] Figure 7 EBSD image of the deposited metal of Comparative Example 2;

[0047] Figure 8 EBSD image of the deposited metal of Comparative Example 3;

[0048] Fig. 9 This is a high-magnification microscopic morphology of the deposited metal of Comparative Example 3 (observed at 5000 times magnification using a scanning electron microscope);

[0049] Fig.10 The inclusion size distribution of Example 1, Comparative Example 2 and Comparative Example 3 and the corresponding inclusion morphology in the impact fracture. DETAILED DESCRIPTION

[0050] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0051] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0052] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0053] In the present invention, the composition design of the 1000MPa grade high strength steel submerged arc welding flux modified by micron-grade rare earth cerium additive is as follows:

[0054] CaF 2 :It can make slag, effectively reduce the melting point, viscosity and surface tension of slag, thereby enhancing the fluidity of slag, and reducing gas impurities in the deposited metal, which is helpful for gas discharge, has a certain dehydrogenation effect, and can reduce the content of diffusible hydrogen in the deposited metal; at the same time, CaF 2 It can also participate in metallurgical reactions, play a role in deoxidation and desulfurization, and improve the quality of deposited metal; in addition, CaF 2 The fluorine gas produced during decomposition has a certain cleaning effect and helps to reduce inclusions in the deposited metal.

[0055] MgO: It is one of the slag-forming components in the flux. It can improve the fluidity of the slag and help improve the forming of the deposited metal. At the same time, MgO also has a certain alkalinity, which can neutralize the acidic substances in the welding process, reduce the hydrogen content of the deposited metal, improve the deposited metal's resistance to cold cracking, enhance the impact toughness of the deposited metal, and improve the welding process performance.

[0056] SiO 2 :It plays the role of slag formation and deoxidation in the flux. The appropriate amount of SiO 2 It can reduce the basicity of the flux, form a stable slag, and protect the deposited metal from oxidation; SiO 2It can also combine with oxygen in the deposited metal to reduce oxide inclusions in the deposited metal, improve the purity of the deposited metal and 2 The synergistic effect affects the anti-porosity and anti-corrosion properties of the flux; in addition, the needle-shaped and fibrous crystal forms used in the present invention can increase the particle strength and reduce the degree of particle crushing in the flux.

[0057] Al 2 O 3 :It is a high melting point oxide that increases the surface tension of the slag. It is an adjuster of the slag viscosity and the basicity of the flux. It can increase the melting point of the flux and enhance the stability of the slag. During the welding process, it helps to reduce the oxidation and nitridation of the deposited metal and improve the mechanical properties of the deposited metal. At the same time, it can also form stable compounds and benign inclusions with other elements in the deposited metal, reducing the proportion of harmful inclusions.

[0058] CaO: It is one of the alkaline oxides in the flux and the main component of the slag. It regulates the alkalinity of the slag, enhances the deoxidation and desulfurization capabilities of the slag, and effectively improves the flux's ability to resist large currents, and improves the surface tension and interfacial tension of the slag. In addition, CaO can also form stable compounds with other elements in the deposited metal, such as Mn and Si, to reduce inclusions in the deposited metal.

[0059] TiO 2 :Improve the viscosity and interfacial tension of the slag, promote the discharge of the slag system during welding, stabilize the arc, reduce the spatter and smoke generation during welding, and improve the welding environment; at the same time, TiO 2 It can also form stable compounds with elements such as Si, Mn, Al in the deposited metal, reducing inclusions and porosity defects in the deposited metal.

[0060] MnO: reacts with SiO during welding 2 It combines to form composite silicates and generates good welding slag to protect the deposited metal from the influence of N and O in the air. The reduced Mn element can improve the strength and impact toughness of the deposited metal, and combine with S in the deposited metal to form MnS, which plays a role in removing S, thereby reducing the tendency of hot cracking.

[0061] Micron-sized rare earth cerium: Rare earth cerium can change the type, distribution and morphology of inclusions through complex metallurgical reactions such as substitution, generating more fine, uniform, dispersed and spherical composite inclusions. These inclusions can generate low-density, high-melting-point rare earth oxides and sulfides in the high-temperature molten pool and the subsequent cooling process to purify the deposited metal; the reduction in the proportion of large-sized non-spherical harmful inclusions will also increase the uniformity of the molten pool, thereby increasing the melt wetting angle, improving the fluidity of the molten pool, and ensuring the stability of the welding process. At the same time, the complex rare earth cerium inclusions that have not entered the slag can become heterogeneous nucleation cores, increasing the strength and toughness of the deposited metal, and enhancing the corrosion resistance of the deposited metal; the addition of cerium will also change the melting point of the flux through interaction with other elements. The flux with a lower melting point is easier to melt and flow during welding. The reduction of impurities will also increase the uniformity of the molten pool, thereby increasing the melt wetting angle, improving the fluidity of the molten pool, and ensuring the stability of the welding process; rare earth cerium inclusions can also induce the nucleation of acicular ferrite, through the surface Ce 2 O 2 S.Ce 3 S 4 Compounds such as CeS promote the formation of acicular ferrite, refine grains, prevent crack propagation, and increase the tensile strength and yield strength of the deposited metal; in addition, cerium can also improve organizational properties by solid solution strengthening and affecting each stage of grain growth.

[0062] Example 1

[0063] The chemical composition of the flux provided in this embodiment, measured by weight percentage, includes: CaF 2 :25%,MgO:30%,SiO 2 : 10%,Al 2 O 3 :15%, CaO:6%, TiO 2 : 5%, K 2 O+Na 2 O: 6%, MnO: 1%, micron-sized rare earth cerium additive: 2%, K 2 O+Na 2 O in K 2 O and Na 2 The mass ratio of O is 1:3. The specific composition of the flux is shown in Table 2.

[0064] The preparation method of the above flux comprises:

[0065] Preparation of micron-sized rare earth cerium additive: First, cerium trifluoride is prepared by chemical reaction method. The method is to oxidize and roast rare earth cerium mineral (Baotou ore) at 400°C for 50 minutes to obtain roasted mineral, and then leach the roasted mineral with 4 mol / L nitric acid solution at a solid-liquid ratio of 3 for 70 minutes to obtain a leachate. Ce is extracted from the leachate by neutral phosphorus extractant Cyanex923. 4+ and F - Then, 0.1% H 2 O 2 Reduction stripping is performed to obtain nano cerium trifluoride, and the cerium trifluoride is roasted in a muffle furnace at 300°C for 30 minutes to obtain high-purity cerium trifluoride (purity> 99.95%), and then the cerium trifluoride prepared by the chemical reaction method is ultrasonically washed with distilled water for 30 minutes, and then dried at 150°C for 6 hours, and then calcined according to the step temperature system of 500°C / 2h+700°C / 2h+900°C / 2h+1200°C / 2h, Subsequently, the powder is crushed and ground by a small cone crusher under the conditions of room temperature and humidity <50%, and then sieved by an ultrasonic vibration sieve machine, the mesh numbers of the sieves are 50, 80, 100, and 150 meshes, and then ball-milled again under the same environment and sieved through a 200-mesh sieve to obtain a micron-grade rare earth cerium additive powder (cerium trifluoride) with a particle size of 50-100 μm and a melting point of 900-1640°C, which is placed in a vacuum packaging bag and evacuated, and then the flux is prepared according to the following steps:

[0066] Step 1: Powder preparation: except for the micron-sized rare earth cerium additive, K 2 O+Na 2 The other ingredients except O are canned according to the flux formula. The specific ingredients are shown in Table 2. Prepare the micron-grade rare earth cerium additive;

[0067] Step 2: Stirring; put the batching tank into a mixer filled with argon and dry stir the powder for 10 minutes at a speed of 120 rpm, put the micron-sized rare earth cerium additive into the atomizer, and connect the atomizer to the mixer to start atomization. The atomization pressure is 4MPa. Stir at a speed of 60 rpm for 20 minutes while atomizing to make the micron-sized rare earth cerium additive atomized into tiny particles fully mixed with other components in the flux. Among them, when the micron-sized rare earth cerium additive is introduced, the spherical particles with a particle size of 40 to 100 μm account for the largest proportion, which is 80%, and then 6% K is added. 2 O+Na 2 O, that is, the introduction of water glass, so that the K in the added water glass 2 O+Na 2 O content is 6% of the flux, stirring at 60 rpm for 20 min;

[0068] Step 3: Granulation: The wet mixture prepared in step 2 is passed into a disc-type rotating granulator for granulation at a speed of 200 rpm;

[0069] Step 4: low temperature drying; the material granulated in step 3 is transferred to a rotary continuous low temperature drying furnace at a drying temperature of 200°C;

[0070] Step 5: low temperature screening; the material dried at low temperature in step 4 is passed into a vibrating screening machine for screening, and the screening particle size range is 12 to 50 mesh;

[0071] Step 6: high temperature sintering; the material obtained in step 5 is transferred into a rotary continuous high temperature drying furnace at a drying temperature of 750°C;

[0072] Step 7: high temperature screening; the material after high temperature sintering in step 6 is further screened and optimized by a vibrating screening machine, and the screening particle size range is 12 to 50 mesh;

[0073] Step 8: Cooling: The material produced in step 7 is transferred into a rotary continuous cooling furnace, and the cooling method is outer wall air cooling;

[0074] Step 9: Packaging: Packing the cooled powder to obtain flux.

[0075] After the flux is obtained, the welding wire with the composition shown in Table 1 is used to perform submerged arc welding on the base material high-strength steel B950CF according to the process parameters in Table 4. The groove form is a 45° V-groove, and the size of the welding test plate is 350 mm×300 mm×20 mm.

[0076] The mechanical property test results of the deposited metal obtained by welding the flux and the welding wire adopted in this embodiment are shown in Table 5.

[0077] The metallographic structure magnification (500 times) and high-magnification microscopic morphology (3000 times) of the deposited metal obtained in this embodiment are as follows: Figure 1 , Figure 3 As shown in the figure, the impact fracture morphology of the deposited metal is shown in Figure 4 The EBSD image of the deposited metal is shown in Figure 6 As shown in the figure, the size distribution of inclusions in the deposited metal and the corresponding morphology of inclusions in the impact fracture are shown in Fig.10 shown.

[0078] Comparative Example 1

[0079] The difference between this comparative example and Example 1 is that only 50 mesh screening is performed during the preparation of the micron-sized rare earth cerium additive, resulting in a larger particle size of the additive. The remaining steps and process parameters are the same as those of Example 1.

[0080] The mechanical properties test results of the deposited metal obtained by welding the flux and welding wire adopted in this comparative example are shown in Table 5.

[0081] The metallographic structure of the deposited metal obtained in this comparative example is magnified (500 times) as shown in Figure 2 shown.

[0082] Comparative Example 2

[0083] The difference between this comparative example and Example 1 is that K 2 O+Na 2 O is 8%, no micron-sized rare earth cerium additive is added, and the remaining steps and process parameters are the same as those in Example 1.

[0084] The mechanical properties test results of the deposited metal obtained by welding the flux and welding wire adopted in this comparative example are shown in Table 5.

[0085] The impact fracture morphology of the deposited metal obtained in this comparative example is shown in Figure 5 The EBSD image of the deposited metal is shown in Figure 7 As shown in the figure, the size distribution of inclusions in the deposited metal and the corresponding morphology of inclusions in the impact fracture are shown in Fig.10 shown.

[0086] Comparative Example 3

[0087] The difference between this comparative example and Example 1 is that the flux provided in this comparative example contains CaF 2 The amount of the micron-sized rare earth cerium additive is 23%, and the amount of the micron-sized rare earth cerium additive is 4%. The remaining steps and process parameters are the same as those in Example 1.

[0088] The mechanical properties test results of the deposited metal obtained by welding the flux and welding wire adopted in this comparative example are shown in Table 5.

[0089] The EBSD image of the deposited metal obtained in this comparative example is as follows: Figure 8 As shown in the figure, the high-magnification microscopic morphology (5000 times) of the deposited metal is as follows Fig. 9 As shown, spectra 96, 97, and 98 are brittle phases precipitated at grain boundaries when rare earth is excessive in the deposited metal. The size distribution of inclusions in the deposited metal and the corresponding inclusion morphology in the impact fracture are shown in Fig.10 shown.

[0090] The welding wire compositions of Example 1 and Comparative Examples 1 to 3 are shown in Table 1, and the flux compositions of Example 1 and Comparative Examples 1 to 3 are shown in Table 2.

[0091] Table 1 Chemical composition of welding wire (by weight percentage, %)

[0092] experiment C Si Mn S P Cr Ni Mo Fe Example 1 0.12 0.20 1.8 0.005 0.007 0.5 2.8 0.8 margin Comparative Example 1 0.12 0.20 1.8 0.005 0.007 0.5 2.8 0.8 margin Comparative Example 2 0.12 0.20 1.8 0.005 0.007 0.5 2.8 0.8 margin Comparative Example 3 0.12 0.20 1.8 0.005 0.007 0.5 2.8 0.8 margin

[0093] Table 2 Chemical composition of flux (by weight percentage, %)

[0094] experiment <![CDATA[CaF 2 ]]> <![CDATA[SiO 2 ]]> MgO <![CDATA[TiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> CaO <![CDATA[K 2 O+Na 2 Of]]> MnO Rare Earth Cerium Additive Example 1 25 10 30 5 15 6 6 1 2 Comparative Example 1 25 10 30 5 15 6 6 1 2 (large particle size) Comparative Example 2 25 10 30 5 15 6 8 1 0(Not added) Comparative Example 3 23 10 30 5 15 6 6 1 4 (overdose)

[0095] Table 3 Welding process parameters

[0096]

[0097] Table 4 Mechanical properties of deposited metal obtained in Example 1 and Comparative Examples 1 to 3

[0098]

[0099] The properties of the deposited metal obtained by welding in the embodiment and comparative examples 1 to 3 are described below in conjunction with the accompanying drawings:

[0100] from Figures 1 to 3 , Figures 6 to 8 It can be seen that the deposited metal structure is mainly proeutectoid ferrite and martensite-austenite components (MA components) precipitated at the grain boundaries. A large amount of acicular ferrite is distributed on the deposited metal of Example 1. The fine and dispersed MA components can hinder dislocation movement, reduce stress concentration, and hinder crack propagation. A large amount of acicular ferrite inclusions can increase the volume fraction of ferrite, refine the ferrite grains, and make their shape and distribution more reasonable. The ferrite in the deposited metal of Example 1 has an interlocking structure, which can effectively prevent the expansion of cracks, and the acicular ferrite can completely surround harmful non-metallic inclusion particles, thereby significantly reducing or even eliminating the damage of these inclusions to the plasticity and toughness properties of the material. By comparison Figure 4 , Figure 5 It can be seen that Example 1 ( Figure 4 ) has a large number of dimples in the deposited metal fracture, and the sample is a microporous aggregate fracture, thus showing good plasticity. Example 1 and Comparative Example 2 ( Figure 5 ) are all micropore-aggregated ductile fractures. A small amount of tearing edges can be found at the deposited metal fracture of comparative example 2. The deposited metal fracture of embodiment 1 has deeper dimples and a higher density, showing better toughness.

[0101] The deposited metals of Example 1, Comparative Example 2 and Comparative Example 3 were analyzed using the EBSD phase differentiation function. The results are as follows: Figures 6 to 8 , analysis shows that the retained austenite is distributed along the dendrites and grain boundaries, and the comparative example 2 ( Figure 7 )、Example 1( Figure 6 ), Comparative Example 3( Figure 8) in the deposited metal are 0.25%, 0.51% and 0.41% respectively, which indicates that the participation of appropriate rare earth cerium in the welding process can stabilize the austenite phase. The residual austenite will undergo transformation induced plasticity (TRIP) to martensite during impact deformation, thereby improving the plastic deformation capacity. However, excessive addition of rare earth reduces the residual austenite, and martensite accounts for the majority of the MA component, resulting in reduced toughness of the deposited metal. The toughness phase in the MA component competes with the effect of brittleness on toughness, which is consistent with the performance that the mechanical properties first increase and then decrease. The morphology of the deposited metal grain boundaries of Comparative Example 2 was observed using SEM scanning. Figure 5 It can be seen that excessive addition of cerium will cause the cerium element to segregate at the grain boundaries to form brittle precipitates, which will reduce the mechanical properties of the deposited metal.

[0102] By counting the number and size of inclusions in Example 1, Comparative Example 2, and Comparative Example 3, combined with the impact fracture morphology of the corresponding deposited metals, the results are as follows: Fig.10 As shown, it can be seen that the average sizes corresponding to Comparative Example 2, Example 1, and Comparative Example 3 are 0.80μm, 0.77μm, and 0.79μm, respectively. In the deposited metal of Example 1, inclusions with a size of 0.6-0.8μm account for the largest proportion, and inclusions with larger sizes account for a smaller proportion. It is calculated that the proportion of inclusions of various sizes has a certain influence on the correlation coefficient r of -60℃ impact toughness. Inclusions with a size of 0.6-0.8μm are highly positively correlated with -60℃ impact toughness, and inclusions larger than 0.8μm are negatively correlated with impact performance. The larger the average size of the inclusions, the greater the negative impact on the impact, indicating that small-sized inclusions (0.6-0.8μm) have a positive effect on improving low-temperature impact toughness; with the increase of rare earth cerium addition, the size of the inclusions increases, the cerium element is segregated, the size of the inclusions increases, and they accumulate at the dimples to become crack sources that damage the properties of the deposited metal, so that excessive addition of rare earth cerium has a reverse effect.

[0103] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A 1000MPa grade high strength steel submerged arc welding flux modified by a micron grade rare earth cerium additive, characterized in that: The chemical composition of the flux, measured by weight percentage, includes: CaF2: 23-29%, MgO: 28-35%, SiO2: 8-15%, Al2O3: 14-20%, CaO: 6-10%, TiO2: 5%, K2O+Na2O: 5-10%, MnO: ≤4%, micron-grade rare earth cerium additive: ≤2%; The mass ratio of K2O to Na2O in the K2O+Na2O is 1:

3.

2. The flux according to claim 1, characterized in that The micron-grade rare earth cerium additive in the flux is 1-2% by weight.

3. A method for preparing the flux according to claim 1, characterized in that: include: (1) preparing high-purity cerium trifluoride by chemical reaction method, and then subjecting the cerium trifluoride to ultrasonic washing, drying, step temperature calcination, grinding, screening, ball milling, and secondary screening to obtain a micron-grade rare earth cerium additive; (2) except for the micron-sized rare earth cerium additive and K2O+Na2O, the other ingredients are mixed and canned according to the flux formula, and the mixing tank is placed in a mixer filled with rare gas for dry mixing; (3) loading the micron-sized rare earth cerium additive into an atomizer, connecting the atomizer to a mixer, and simultaneously starting the atomization and stirring process to atomize the micron-sized rare earth cerium additive into tiny particles and fully mix them with other components in the flux; (4) After the atomization is completed, K2O+Na2O is added and stirred. After being stirred evenly, the flux is obtained through granulation, low-temperature drying, low-temperature screening, high-temperature drying, high-temperature screening, cooling and packaging steps.

4. The preparation method according to claim 3, characterized in that: (1) The purity of cerium trifluoride obtained by the chemical reaction method is greater than 99.95%; the drying temperature is 100-200°C, and the drying time is 6 hours; the step temperature calcination system is 500°C / 2h+700°C / 2h+900°C / 2h+1200°C / 2h; the mesh sizes of screening are 50, 80, 100, and 150 meshes respectively; the mesh size of secondary screening is 200 meshes; grinding, screening, ball milling, and secondary screening are all carried out at room temperature and low humidity.

5. The preparation method according to claim 3, characterized in that: (1) The particle size of the medium-micron rare earth cerium additive is 50-100 μm, and the melting point is 900-1640°C.

6. The preparation method according to claim 3, characterized in that: (2) The medium-dry mixing time is 5 to 10 minutes, and the rotation speed is 120 rpm.

7. The preparation method according to claim 3, characterized in that: (3) The atomization pressure of the atomization process is 3.5-5.0 MPa; the stirring time is 20 min, and the rotation speed is 60 rpm.

8. The preparation method according to claim 3, characterized in that: (4) The medium and low temperature drying temperature is 200-300°C; the low temperature screening mesh is 12-50 mesh; the high temperature drying temperature is 750-850°C; the high temperature screening mesh is 12-50 mesh.

9. Use of the flux according to any one of claims 1 to 2, characterized in that: This flux is used for welding 1000MPa grade high-strength steel in hydropower projects.

10. A deposited metal obtained by the application of claim 9, characterized in that: Tensile strength ≥950MPa, yield strength ≥820MPa, -40℃ impact absorption energy ≥85J, -60℃ impact absorption energy ≥70J.

Citation Information

Patent Citations

  • Submerged arc automatic welding sintering welding flux used for 1000 MPa high-strength steel and preparing method

    CN108637527A